Philippi : Stadt und Christengemeinde zur Zeit des Paulus - Bormann, Lukas. (Novum Testamentum, Supplements, 1995)
The Roman colony of Philippi is the site upon which Paul founded his first European congregation. There, he encountered a political entity which bore the stamp of Roman culture through and through. Part I describes Philippi's political and religious situation based on numismatic, epigraphical, archaeological and literary sources. Part II reconstructs the relationship between Paul, the congregation, and the city of Philippi, and demonstrates the influence which the Roman environment exerted on the church's organization and preaching. The work reaches the conclusion that the Philippean community assumed an active and self-confident role in implementing its mission. In so doing, it clashed with the Roman authorities and their insistence upon a religious praxis that did not call into question the principles or existence of the Roman State. The book contributes to the interpretation of the Epistle to the Philippians as well as to the history of early Christianity and the history of Religions during the first century.